Peran Guru PAI dalam Mengembangkan Sikap Kemandirian Siswa (Studi Kasus di Marhalah Tsanawiyah TMI Putri Al-Amien Prenduan) - Izzat Amini; Siti Jamilah (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2023)
This study addresses the issue of students' lack of independence, influenced by various factors including inherent traits, environment, parenting style, birth order, and economic circumstances. The role of Islamic Religious Education (PAI) teachers goes beyond knowledge transmission, requiring an understanding of students' diverse characteristics to foster independence. This research focuses on Marhalah Tsanawiyah TMI Putri Al-Amien Prenduan as a case study. The objectives are to (1) explore the role of PAI teachers in cultivating students' independence attitudes and (2) identify the steps taken to foster independence in the same context. Employing a qualitative field research approach, data is collected through interviews, observations, and documentation. Data analysis involves reduction, presentation, and drawing conclusions, with validity ensured through triangulation. Findings reveal that PAI teachers play multiple roles as educators, managers, supervisors, and motivators to foster independence. Strategies employed include providing guidance for emotional independence and instilling problem-solving skills to promote behavioral independence. This research contributes insights into enhancing students' independence in the context of Islamic religious education.